Effectiveness of Playing Picture Cards on Language Development in Preschool Children (4-5 Years) - Vianita , Imelda Liena (Tarqabin Nusantara Group, 2024)
The ability to speak is one of the ability that must be owned by all children aged 4-5 years. Playing with learning is the stimulus the most effective to enhance the language development. One of game in accordance is a game of the picture. The purpose of this study is to know the effectiveness of playing picture cards to the language development in preschoolers (4-5 years). The methode of this research is Pre-Eksperimental Design using One Group Pra-Post Tes Design with sample of 39 respondents. The sampling technique by purposive sampling using statistical tests